Late-glacial to late-Holocene shifts in global precipitation δ18O - Jasechko, S.; Lechler, A.; Pausata, F. S. R.; Fawcett, P. J.; Gleeson, T.; Cendón, D. I.; Galewsky, J.; LeGrande, A. N.; Risi, C.; Sharp, Z. D.; Welker, J. M.; Werner, M.; et al. (Climate of the Past, 2015)
Abstract. Reconstructions of Quaternary climate are often based on the isotopic content of paleo-precipitation preserved in proxy records. While many paleo-precipitation isotope records are available, few studies have synthesized these dispersed records to explore spatial patterns of late-glacial precipitation δ18O. Here we present a synthesis of 86 globally distributed groundwater (n = 59), cave calcite (n = 15) and ice core (n = 12) isotope records spanning the late-glacial (defined as ~ 50 000 to ~ 20 000 years ago) to the late-Holocene (within the past ~ 5000 years). We show that precipitation δ18O changes from the late-glacial to the late-Holocene range from −7.1 ‰ (δ18Olate-Holocene > δ18Olate-glacial) to +1.7 ‰ (δ18Olate-glacial > δ18Olate-Holocene), with the majority (77 %) of records having lower late-glacial δ18O than late-Holocene δ18O values. High-magnitude, negative precipitation δ18O shifts are common at high latitudes, high altitudes and continental interiors (δ18Olate-Holocene > δ18Olate-glacial by more than 3 ‰). Conversely, low-magnitude, positive precipitation δ18O shifts are concentrated along tropical and subtropical coasts (δ18Olate-glacial > δ18Olate-Holocene by less than 2 ‰). Broad, global patterns of late-glacial to late-Holocene precipitation δ18O shifts suggest that stronger-than-modern isotopic distillation of air masses prevailed during the late-glacial, likely impacted by larger global temperature differences between the tropics and the poles. Further, to test how well general circulation models reproduce global precipitation δ18O shifts, we compiled simulated precipitation δ18O shifts from five isotope-enabled general circulation models simulated under recent and last glacial maximum climate states. Climate simulations generally show better inter-model and model-measurement agreement in temperate regions than in the tropics, highlighting a need for further research to better understand how inter-model spread in convective rainout, seawater δ18O and glacial topography parameterizations impact simulated precipitation δ18O. Future research on paleo-precipitation δ18O records can use the global maps of measured and simulated late-glacial precipitation isotope compositions to target and prioritize field sites.